PEMAKNAAN BEBERAPA SIMBOL DARI PENOKOHAN SANTIAGO DALAM NOVEL THE OLD MAN AND THE SEA KARYA ERNEST HEMINGWAY - Jumino, Jumino (Sabda: Jurnal Kajian Kebudayaan, 2016)
For some people, life means struggle and hard work to achieve their goals. This is experienced by Santiago, the main character of Ersnest Hemingway’s novel translated into Indonesaan entitled The Old Man and the Sea. The way of life seems to be the motto of American people pursuing American dream. However, the spirit is not only the main factor, there are also some factors influencing their acomplishement, such as nature and fate. This reality can be seen from the struggle of Santiago representing American dream to search his fortune.